KNOWLEDGE, ATTITUDE AND PRACTICE OF INFECTION CONTROL AMONG DENTAL PRACTITIONERS IN ISLAMIC INTERNATIONAL DENTAL HOSPITAL,RIPHAH - Rao, Ufaq; Khan, Abdul Razaq; Rizwan, Zarnab; Rizwan, Ghina; Zia, Syed Hamza (Journal of Rawalpindi Medical College, 2023)
Objective: The aim of the study was to investigate the knowledge, attitude and practices among dental practitioners at a dental hospital in Islamabad. Materials and methods: This study consisted of 147 participants. The questionnaire had 21 questions related to vaccination status, barrier techniques infection control practices and awareness. The questionnaire was distributed through Google forms to the participants after taking consent from them. The data was analyzed and tabulated through SPSS version 23. Result: Out of 147, 123 participants responded to our questionnaire. 75.6% of the participants were vaccinated against hepatitis B and 87.8% regularly wash their hands before and after dental treatment.100% of the participants wore and change gloves after each patient. In current study the senior dental practitioners had a relatively poor mean score(4.1%) in terms of knowledge, attitude and practice scores regarding infection control as compared to house officers and fresh graduates (59%). 1) Conclusion: The infection control knowledge, attitude and practices among dental practitioners was better, however there is room for improvement in compliance and knowledge in the dental health care workers. More knowledge about infection control measures should be provided to the dental practitioners, moreover efforts are needed to improve the attitude and practice of the dental practitioners towards infection control at Islamic International Dental Hospital, Islamabad.